Color tuning via adjusting the dye-loading capacity of a polymer - Hu, Wei (Langmuir : the ACS journal of surfaces and colloids, 2009)
Color tuning from monomer emission to aggregate emission was accomplished by vacuum thermal evaporation of N,N'-di(n-butyl)quinacridone onto UV-cured photopolymer (NOA-63) with different exposure time. The diffusion of dye molecules into the polymer matrix can be controlled by varying the curing time, which induces the change in the mole ratio between the monomers that are molecularly dispersed into polymer and the aggregates that are shielded on the polymer surface. On the basis of this principle, dual-color and multicolor luminescence patterning were demonstrated by depositing dye molecules onto photolithographically patterned NOA-63 with binary masks and grayscale masks, respectively